DARI KI HAJAR KE GENERASI ALFA : RELEVANSI LANDASAN PENDIDIKAN SOSIOLOGIS INDONESIA DI ERA 5.0 BY SYSTEMATIC LITERATUR RIVIEW - Nur Elih; Didit Kurniadi; Elin Yufriani; Mutoharoh (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to examine the relevance of Indonesian sociological educational foundations inherited from Ki Hajar Dewantara in responding to the characteristics of Generation Alpha in the Society 5.0 era. Social changes driven by technological advancement, digitalization, and artificial intelligence require educational systems to remain rooted in cultural, humanistic, and national values while being adaptive to global challenges. This research employs a qualitative approach using the Systematic Literature Review (SLR) method. Data were collected from national and international journal articles indexed in Google Scholar and indexed SINTA between 2015 and 2025. The literature selection process followed identification, screening, eligibility, and thematic analysis stages. The findings indicate that Ki Hajar Dewantara’s educational principles, such as ing ngarso sung tulodo, ing madya mangun karso, and tut wuri handayani, remain highly relevant as a foundation for character building, social literacy, and independent learning among Generation Alpha. Integrating these sociological values with digital technology utilization strengthens a humanistic, inclusive, and sustainable education system in the Society 5.0 era. This study emphasizes the importance of harmonizing local wisdom and technological innovation in developing an adaptive and competitive national education ecosystem. Keywords: sociological basic of education, Ki Hajar Dewantara, Generation Alpha, Society 5.0.